Effects of the noncompetitive N-methyl-D-aspartate receptor antagonist ketamine on visual signal detection performance in rats. Issue 5 (August 2015) - Hillhouse, Todd M.; Merritt, Christina R.; Porter, Joseph H.
Abstract : The noncompetitive N -methyl-D-aspartate receptor antagonist ketamine produces consistent, rapid, and sustained antidepressant effects in patients suffering from treatment-resistant depression. However, ketamine-induced cognitive impairments remain a major concern. The present study sought to extend the preclinical evaluation of ketamine-induced cognitive impairments by evaluating the dose (1.0–18.0 mg/kg) and time-course (10 min–24 h) of effects of ketamine on sustained attention using a visual signal detection procedure in rats. Overall, ketamine (10.0–18.0 mg/kg) dose-dependently decreased percent hit and correct rejection accuracy. Additionally, these same doses of ketamine increased response latency and trial omissions. In the time-course study, treatment with 18.0 mg/kg ketamine produced the greatest decrease in visual signal detection performance at 10 min, when ketamine decreased percent hit and correct rejection accuracy as well as increased response latency and trial omissions, but returned to saline baseline controls by 100 min. In conclusion, acute ketamine inhibited sustained attention in rats performing a visual signal detection task; however, these effects were short in duration, similar to the short duration (<2 h) of psychotomimetic effects reported in low-dose ketamine treatment in depressed patients.